Proposal of a hydraulic system and the influence on the operation and maintenance of the storm drain in the city of Huanuco - Villalobos Pujaj, Walter Karol (2025)
Objective. Raise the proposal of a hydraulic system that contributes to the operation and maintenance of the storm drainage of the city of Huánuco - 2018. Methods. Study of quantitative approach, correlational scope and experimental design of a quasiexperiment type, the population is the entire pluvial drainage of the City of Huánuco (main and secondary collectors) with a length of 12,921.00 ml., The sample being the collectors: Seichi Izumi, Tarapacá, Huánuco and Dámaso Beraún, whose total length is 7,440.25 ml. Results. It was determined that the amount of sediments that are dragged by the Jactay creek is 2890 m3 / km2 / year, the influence of the project is approximately 0.1378 km2 for each of the critical shreds under evaluation, direct sedimentation in the entire area of The influence of the research is 1.09 m3 / day, thus determining the existence of favorable slopes up to 50% of what was projected and a required water availability of 0.023m3 / sec. Conclusion. With the approach of a hydraulic system, a total dragging of sediment from the interior of the main and secondary collectors is achieved, reaching 100% efficiency of the operation and maintenance of the storm drain.